Nanoparticle-Mediated Delivery of STAT3 Inhibitors in the Treatment of Lung Cancer - Qiyi Feng; Kai Xiao (MDPI AG, 2022)
Lung cancer is a common malignancy worldwide, with high morbidity and mortality. Signal transducer and activator of transcription 3 (STAT3) is an important transcription factor that not only regulates different hallmarks of cancer, such as tumorigenesis, cell proliferation, and metastasis but also regulates the occurrence and maintenance of cancer stem cells (CSCs). Abnormal STAT3 activity has been found in a variety of cancers, including lung cancer, and its phosphorylation level is associated with a poor prognosis of lung cancer. Therefore, the STAT3 pathway may represent a promising therapeutic target for the treatment of lung cancer. To date, various types of STAT3 inhibitors, including natural compounds, small molecules, and gene-based therapies, have been developed through direct and indirect strategies, although most of them are still in the preclinical or early clinical stages. One of the main obstacles to the development of STAT3 inhibitors is the lack of an effective targeted delivery system to improve their bioavailability and tumor targetability, failing to fully demonstrate their anti-tumor effects. In this review, we will summarize the recent advances in STAT3 targeting strategies, as well as the applications of nanoparticle-mediated targeted delivery of STAT3 inhibitors in the treatment of lung cancer.